A new host cell internalisation pathway for SadA‐expressing staphylococci triggered by excreted neurochemicals. (7th June 2019) - Luqman, Arif; Ebner, Patrick; Reichert, Sebastian; Sass, Peter; Kabagema‐Bilan, Clement; Heilmann, Christine; Ruth, Peter; Götz, Friedrich
Abstract: Staphylococcus aureus is a facultative intracellular pathogen that invades a wide range of professional and nonprofessional phagocytes by triggering internalisation by interaction of surface‐bound adhesins with corresponding host cell receptors. Here, we identified a new concept of host cell internalisation in animal‐pathogenic staphylococcal species. This new mechanism exemplified by Staphylococcus pseudintermedius ED99 is not based on surface‐bound adhesins but is due to excreted small neurochemical compounds, such as trace amines (TAs), dopamine (DOP), and serotonin (SER), that render host cells competent for bacterial internalisation. The neurochemicals are produced by only one enzyme, the staphylococcal aromatic amino acid decarboxylase (SadA). Here, we unravelled the mechanism of how neurochemicals trigger internalisation into the human colon cell line HT‐29. We found that TAs and DOP are agonists of the α2‐adrenergic receptor, which, when activated, induces a cascade of reactions involving a decrease in the cytoplasmic cAMP level and an increase in F‐actin formation. The signalling cascade of SER follows a different pathway. SER interacts with 5HT receptors that trigger F‐actin formation without decreasing the cytoplasmic cAMP level. The neurochemical‐induced internalisation in host cells is independent of the fibronectin‐binding protein pathway and has an additive effect. In a sadA deletion mutant, ED99Δ sadA, internalisation was decreased approximately threefold compared with that of the parent strain, and treating S. aureus USA300 with TAs increased internalisation by approximately threefold. Abstract : Particularly animal pathogenic staphylococcal species contain SadA, an enzyme that converts aromatic amino acids (AAAs), L‐DOPA and 5HTP into corresponding trace amines (TAs), dopamine (DOP) and serotonin (SER), respectively. These neurotransmitters boost the internalization of the bacteria by host cells about 2–3 fold. The signaling of TAs and DOP occurs by activation of the α2‐adrenergic receptor (α2‐AR), while SER activates the 5HT receptors. Ultimately, both pathways cause actin polymerization in the host cell, thus mediating the internalization of bacteria.